New high-yielding, stress-resilient, and nutritious crop varieties - Okori, Patrick; Chirwa, Rowland; Chisale, Virginia; Jumbo, McDonald Bright; Makumba, Wilkson; Makumbi, Dan; Matumba, Annie; Mosha, Inviolate; Munthali, Wills; Ganga Rao, Nadigatla V.P.R.; Ngowi, Peter; Njeru, James; et al. (CAB International, 2022)
This chapter describes the performance of new cereal and legume crop varieties introduced by Africa RISING into agroecosystems in which they had not been tested before. The introduced varieties are characterized by their resilience to drought and/or their improved nutritional content.